Menganalisis Alat Evaluasi Pada Mata Pelajaran IPA Siswa Kelas V di SDN 105292 Bandar Klippa Kecamatan Percut Sei Tuan - Dini Puspa Sari; Octariani Br Manik; Widya Ramadhani Lubis; Syahrial Syahrial (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The aim of this research is 1) to find out what assessments are used in science subjects at Riigi Algkooli 105292 Bandar Klippa, Percut Sei Tuan District, Class V, 2) to analyze the quality of assessment tools according to the rules. reliability and competence. Class V Science Exam Difficulties and Different Advantages of SD Negeri 105292 Bandar Klippa, Percut Sei Tuan District. The research method used is descriptive qualitative, namely. description of phenomena that occur in reality. All subjects were class V students at SD 105292 Bandar Klippa. As a primary data source, data sources are obtained from teachers and students, and as secondary data sources, documentation and questionnaires. Data was collected through observation, questionnaires and tests. Meanwhile, data analysis was carried out using validation tests, test reliability, difficulty and distinguishing power. Validation was carried out by the researchers themselves and the validation expert group. Based on the results of observations, it is known that the question format used by teachers in evaluating scientific learning is multiple choice questions consisting of 15 questions, filler questions consisting of 10 numbers, and descriptive questions consisting of 10 questions. 15 questions. of 5 questions. The results of the validation test show that not all multiple choice questions are valid, only 4 out of 15 questions are valid. The form has 5 valid questions and all descriptive questions are recognized as valid. Expert validation also showed that of the 4 experts, only 1 expert showed that the results were quite valid, 3 validation experts showed that the questions were less valid. The reliability test shows that the multiple choice questions are not reliable, while the fill-in-the-blank and description questions are considered reliable. The difficulty level test shows that multiple choice questions have 3 categories of difficulty, namely hard, medium and easy questions, while for questions that can be filled in and are descriptive, only 2 categories of difficulty are found, namely. intermediate questions and easy questions. Finally, the differential power test shows that multiple choice questions have 4 different power categories, namely poor, sufficient, good, and very good. Meanwhile, there were excellent results on questions about filling in and describing different styles.